G347(P) Communication skills with children and parents: foundation doctors' self-reported competence. (24th May 2017) - Hughes, EC; Baker, P
Abstract : Aims: Newly qualified doctors must competently interact with and manage children and young people. Both the General Medical Council (GMC) and the Royal College of Paediatrics and Child Health (RCPCH) have produced expectations for the undergraduate teaching of paediatric specific communication skills. This study assessed the self-reported competence of foundation doctors in communication skills with children and parents, thus evaluating the effectiveness of current paediatric communication skills teaching provided across undergraduate medical schools. Methods: Surveys were distributed among foundation doctors, in paper form and electronically, with both forms containing identical questions. Paper questionnaires were opportunistically handed out at compulsory teaching sessions. Administrators at a number of different hospitals distributed a link to the online survey. Results: 96 questionnaires were returned. 43% of foundation doctors surveyed had worked in a job involving contact with children and 56% had already been in a situation where they required communication skills with children and parents professionally. 41% reported no formal undergraduate paediatric communication skills teaching and 35% felt their teaching was inadequate. However, longer paediatric placements and completing a specialist study component (SSC) in paediatrics were associated with higher levels of confidence in paediatric specific communication skills. Conclusion: This work provides evidence that current undergraduate paediatric teaching may not adequately prepare foundation doctors with communication skills necessary for competent interaction with children and young people. It also highlights the frequency with which foundation doctors come into contact with children and their parents, and the potential benefits of longer placements and SSCs for improving confidence. Although these observations are limited given the number of surveys returned, the dearth of research into paediatric specific communication skills teaching supports the argument that there are inconsistencies in the undergraduate teaching of this subject that need addressing. These results will help to inform the next stage of this work; development of a workshop focussing on the specific challenges posed by the triadic communication involving practitioner, child and parent. The results should also help inform those designing undergraduate curricula of the importance of ensuring GMC and RCPCH expectations of paediatric communication skills teaching are met in order to develop safe, competent practitioners.